Architecture and Power in the University City of Lisbon. Political Dimensions of a Project from the Salazarist Dictatorship - Moura Soares, Clara; Neto, Maria João (CIAN-Revista de Historia de las Universidades, 2025)
This article aims to focus on the political dimension of the University City of Lisbon (Portugal) project. It seeks to establish not only the ideological and aesthetic principles underlying its construction in the 1950s, during the dictatorial Estado Novo regime led by António de Oliveira Salazar (1889-1970), but also key events that took place there and which would prove decisive in the end of the longest authoritarian regime in Western Europe in the 20th century. The academic crisis of 1962 was the first to unfold in the newly inaugurated University City of Lisbon. With a decisive impact on weakening the regime and transforming university spaces into places for asserting freedom, successive academic crises would play a pivotal role in the fall of the dictatorship in 1974, a regime that had ruled the country for more than four decades. These crises also contributed to the enrichment of the Spiritus Loci of the University City of Lisbon, as reflected in its designation as a National Monument in 2023.